Contextual Effect of Integrated Health Post on the Community Health Personnel Performance: A Multilevel Evidence from Purworejo, Central Java - Ulfah Hidayati; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2020)
Background: Integrated health post (posyandu) is an effort to improve the health of the nearest infants in the community. The community health personnel are in charge of managing and carrying out posyandu activities. Community health personnel performance influences the success of the posyandu program. This study aimed to determine posyandu contextual factors on the performance of community health personnels in infant health services.Subjects and Method: This was a cross sectional study conducted at 25 posyandu in Purworejo Regency, Central Java, in October 2019. The sample consisted of 200 community health personnels selected by simple random sampling. The dependent variable was community health personnel performance. The independent variables were number of children, education, occupation, income, tenure, skills and work environment. The data was collected by questionnaire. The data were analyzed by multilevel multiple logistic regression.Results: Posyandu community health personnel performance increased with the number of children <3 (b = 1.89; 95% CI= 0.51 to 3.26; p = 0.007), education ≥Senior high school (b= 1.88; 95% CI = 0.31 to 3.44; p= 0.019), community health personnels worked at home (b= 2.15; 95% CI= 0.48-3.82; p = 0.011), income ≥Rp 1,200,000 (b= 1.86; 95% CI= 0.19-3.54; p= 0.029), tenure ≥3 years (b= 2.29; 95% CI= 0.71 to 3.87; p= 0.005), good skills (b= 2.34; 95% CI= 0.53 to 4.16; p = 0.011), and good working environment (b= 1.54; 95% CI= 0.01 to 3.06; p= 0.048). Posyandu had a contextual effect on community health personnel performance with ICC= 34.98%.Conclusion: Community health personnel performance increases with the number of children <3, education ≥senior high school, community health personnels working at home, family income ≥Rp 1,200,000, working period ≥ 3 years, good skills, and good work environment. Posyandu has a contextual effect on community health personnel performance.Keyword: performance, community health personnels, posyandu, multilevel analysisCorrespondence: Ulfah Hidayati. Master Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java. Email: ulfahhidayatimg13@gmail.com. Mobile: +6285725932516.Journal of Health Policy and Management (2020), 5(1): 1-12https://doi.org/10.26911/thejhpm.2020.05.01.01